International Students: The United Kingdom Drops the Ball - Marginson, Simon (International Higher Education, 2014)
The number of non-EU students entering UK higher education has fallen for the first time for many year, especially students from South Asia. The UK government is under pressure from the neo-nationalist UK independence Party to reduce all forms of migration and international education has been caught by this.